Successful Low-Dose tPA for Mechanical Mitral Valve Thrombosis in a Patient with Postinfarction Contained Left Ventricular Free Wall Rupture. (19th July 2021) - Livesay, James; Isang, Emmanuel; Tahir, Hassan; Baljepally, Raj
Abstract : Prosthetic valve thrombosis is a potentially life-threatening complication diagnosed by a combination of clinical features and imaging modalities, but the optimal management in high bleeding risk patients remains controversial. Current treatment options for prosthetic valve thrombosis included surgery, thrombolytic therapy, and anticoagulation. We present a very unusual case of a patient with a recent ST-elevation myocardial infarction complicated by contained left ventricle free wall rupture and mechanical mitral valve thrombosis. Deemed a high surgical risk candidate, low-dose tissue plasminogen activator was used despite significant bleeding risk from contained left ventricle free wall rupture, which resulted in resolution of the thrombus. To the best of our knowledge, this is the first report of successful thrombolytic therapy for prosthetic mechanical mitral valve thrombosis in a patient with recent postmyocardial infarction contained left ventricular free wall rupture.